OPTIMALISASI KEARIFAN LOKAL PADA PENGAJARAN INTEGRATED LANGUAGE SKILL MENGGUNAKAN METODE BLENDED LEARNING - Elysa Hartati (Share : Journal of Service Learning, 2021)
Culture is an ancestral heritage that contains many moral values to learn. However, the current young generation seems reluctant to learn about the culture in their environment or from the teaching point of view in schools it does not provide a platform to introduce culture to their students. Even though by integrating cultural values in learning, especially language learning, it can add to students' repertoire of loving their own culture because there are many values of local wisdom contained in it. By inserting examples of cultural heritage such as wayang orang, traditional houses, traditional events can be used as interesting learning materials for students because they remind them of the rich ancestral heritage in the texts they are studying. The use of the blended learning method is also a good alternative in optimizing local wisdom in teaching integrated language skills. By utilizing their own devices, they can have access to search for information from various sources such as YouTube, podcasts, and several websites to enrich their understanding of the culture in their environment. From these devices they can also help promote local culture in their environment. And on the other hand, teachers also have a role as cultural promoters through learning materials in the form of texts that they teach.   Abstrak: Masuknya budaya asing yang masif diduga akan membawa penurunan pengakuan budaya lokal oleh generasi muda khususnya anak-anak sekolah. Padahal, budaya lokal tersebut tetap dapat diajarkan secara terpadu dengan menyisipkan kearifan lokal melalui teks yang digunakan sebagai bahan dan media belajar mengajar khususnya pada mata pelajaran bahasa. Artikel ini bertujuan untuk memaparkan bagaimana mengoptimalkan kearifan lokal dalam pengajaran keterampilan berbahasa terpadu melalui metode blended learning. Dengan memanfaatkan pendekatan POACE (Planning, Organizing, Actuating, Controlling, and Evaluating), program pengabdian masyarakat ini dilakukan melalui platform daring berupa workshop. Program ini mendapat respon positif dari 50 peserta guru dan calon guru bahasa yang bergabung. Mereka juga menyadari pentingnya masalah ini untuk mencegah punahnya budaya lokal. Mengintegrasikannya dengan teknologi ke dalam pengajaran bahasa bisa menjadi alternatif yang bisa dilakukan. Para siswa juga dapat mengenali budaya lokal mereka sendiri dengan mendapatkan beberapa teks yang berisi warisan budaya sambil belajar bahasa. Sementara itu, guru juga dapat berperan sebagai promotor budaya melalui materi ajar yang dibawanya ke dalam kelas. Dengan demikian, konservasi budaya dapat dilakukan oleh kedua pihak, yaitu guru dan siswa sebagai generasi muda.